2015
DOI: 10.26443/ijwpc.v2i1.88
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of a diagnosis of incurable cancer: The importance of communication

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A recent study of Bradford et al (2022), regarding AYAs with advanced cancer suggests that coping is a dynamic process where different strategies are used depending on the stressor, available resources and previous experiences. Earlier research on AYAs or adult patients with advanced cancer found acceptance, positive attitude by making comparisons with people in worse situations and setting realistic goals, keeping hope and support seeking as the most commonly used coping strategies (Trevino et al, 2012;Lobb et al, 2015;García-Rueda et al, 2016;Walshe et al, 2017;Lie et al, 2018;Bradford et al, 2022). Arantzamendi et al (2020) redefined the theory of "living well with chronic illness" to explain the experience of living with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of Bradford et al (2022), regarding AYAs with advanced cancer suggests that coping is a dynamic process where different strategies are used depending on the stressor, available resources and previous experiences. Earlier research on AYAs or adult patients with advanced cancer found acceptance, positive attitude by making comparisons with people in worse situations and setting realistic goals, keeping hope and support seeking as the most commonly used coping strategies (Trevino et al, 2012;Lobb et al, 2015;García-Rueda et al, 2016;Walshe et al, 2017;Lie et al, 2018;Bradford et al, 2022). Arantzamendi et al (2020) redefined the theory of "living well with chronic illness" to explain the experience of living with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%